Análise da integração do cadastro único com o CNIS: obstáculos e possibilidades na transformação digital do Governo Federal - Lerbach, Pedro Augusto de Carvalho (2025)
This work aims to analyze the integration process between Brazil’s Social Security Registry – CNIS – and the Single Registry for Social Programs – CadÚnico – regarding the concept of digital transformation and Brazilian policies that focus on this broader social process. Digital transformation is a process that societies have been going through under the influence of recent Information and Communication Technologies – ICTs, which go further than existing digital services like e-mail or the basic use of the internet and systems and impact the way social interaction occur. For instance, there are, artificial intelligence, big data, internet of things, cloud computing, etc. which are often called “disruptive technologies”. Given this technological advance and social change, digital government is a government that goes beyond mere electronic government, thinking and acting in a “digital by default” paradigm, and not merely with a digital alternative to analogic. This process finds difficulties in Social Assistance, given the lack of digital inclusion in the country. However, database integration is an aspect of this transformation, which ameliorates public policy and optimizes service at the frontline. Through semi-structured interviews with public agents who participate in this integration between CNIS and CadÚnico and through analysis of official documents, the research identified institutional elements that, according to the professionals interviewed, smoothens or hinders the process, taking the Brazilian Digital Transformation Strategy and the Digital Government Strategy as background, identifying new research questions, and seeking conclusions that enhance similar processes in the public sector. A thematic and category content analysis guided the development of a historical overview and a detailed description of the integration process. The analysis identified that institutional actors sought legal certainty and emphasized the significance of Constitutional Amendment No. 103, the importance of mutual necessity among stakeholders and the sustained presence of the technical team, and the internal processes of persuasion and conceptual alignment. The findings also indicated the potential influence of corporate interests, the tendency toward data centralization in a limited number of institutions, and other elements. The actors identified that data integration enhances efficiency in conceding social benefits, improves information reliability, and optimizes frontline service. Several limitations persist, including insufficient digital inclusion, conceptual discrepancies across institutions, the manner databases are operated and challenges in aligning diverse organizational interests. Technological issues are increasingly not the main barrier. However, institutions continue to expand database integration efforts, due to the possibilities that the technological advancements offer.